Pengaruh Visual Dagangan dan Rambu Promosi Signage Terhadap Pembelian Impulsif Store Decathlon Mall Kota Kasablanka - Agung Ihza; Imam Wibowo; Richard Saragih (Jurnal Ekonomi dan Industri, 2025)
This study aims (1) to determine the effect of visual merchandising partially on impulsive buying at the Decathlon Mall Kota Kasablanka store. (2) the effect of promotional signage partially on impulsive buying at the Decathlon Mall Kota Kasablanka store. (3) to determine the influence of visual merchandising and promotional signage simultaneously against impulsive buying at the Decathlon Mall Kota Kasablanka Store. This study uses primary data through the distribution of questionnaires to visitors to the Decathlon Mall Kota Kasablanka store. The analysis method used is simple and multiple linear regression analysis. The results of this study show that (1) Visual Merchandising has a positive and significant effect on Impulse Buying. (2) Promotional Signage has a positive and significant effect on Impulse Buying. (3) Visual Merchandising and Promotional Signage simultaneously have a positive and significant effect on Impulse Buying.